1988
DOI: 10.1055/s-2007-999677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supine Exercise on Fetal Heart Rate in the Second and Third Trimesters

Abstract: The effects of a brief period of supine exercise on fetal heart rate (FHR) was studied in 25 healthy, regularly exercising women, 12 in the late second trimester and 13 in the mid third trimester. Although statistically significant increases in maternal mean arterial pressure and pulse occurred, the exercise intensity was mild, with the average percent maximal pulse being 46 +/- 5% and 49 +/- 5% in the second and third trimester groups, respectively. Small increases in FHR were seen in both groups, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…1 22 23 25 26 42–47 56 68 75 77 A post hoc sensitivity analysis was performed removing one trial (n=6 women) demonstrating a decrease in FHR of 58 bpm during exercise1; the impact of prenatal exercise on FHR was similar (mean difference (MD)=7.41 bpm; see online supplement figure 1). Four studies could not be included in the pooled analysis due to missing SD,27 78 missing baseline values79 and insufficient figure quality76 (n=57 women; see online supplement tables 1 and 2 for additional details). Two of these studies demonstrated that in response to a single bout of swimming exercise, FHR was increased by a mean of 2.0 bpm27 and 7.0 bpm 78.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 22 23 25 26 42–47 56 68 75 77 A post hoc sensitivity analysis was performed removing one trial (n=6 women) demonstrating a decrease in FHR of 58 bpm during exercise1; the impact of prenatal exercise on FHR was similar (mean difference (MD)=7.41 bpm; see online supplement figure 1). Four studies could not be included in the pooled analysis due to missing SD,27 78 missing baseline values79 and insufficient figure quality76 (n=57 women; see online supplement tables 1 and 2 for additional details). Two of these studies demonstrated that in response to a single bout of swimming exercise, FHR was increased by a mean of 2.0 bpm27 and 7.0 bpm 78.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies demonstrated that in response to a single bout of swimming exercise, FHR was increased by a mean of 2.0 bpm27 and 7.0 bpm 78. One study demonstrated an increase in FHR by 6 bpm in the second trimester and 9 bpm in the third trimester during 5 min of resistance training exercises 79. We were unable to extract data from a fourth study due to insufficient figure quality; however, the authors reported that FHR did not differ between trimesters at rest and during exercise 76…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute exercise consisted of static exercises (eg, pelvis raised off the floor) held for 5 min (total exercise time 35–40 min),22 abdominal strengthening exercises including pelvic tilts performed for 5 min,19 dynamic floor exercise that included abdominal exercises such as crunches and leg lifts for 10 min,20 and sets of single leg extensions and double leg extensions 23. Intensity (defined as 15 (hard) on the Borg’s Rating of Perceived Exertion 20-point scale) was recorded in only one study 20.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal outcomes were potentially adverse changes in (5) fetal movements, (6) FHR (patterns and fetal bradycardia FHR <110 bpm19), (7) uterine blood flow, (8) low birth weight (small for gestational age (SGA), <2500 g, <10th/15th percentile for gestational age or intrauterine growth restriction (IUGR)), (9) perinatal mortality (death between 20 weeks’ gestation and 28 days of life), and (10) others (as defined and documented by individual study authors). Examples of abnormal FHR patterns included absent (non-reactive) baseline FHR variability in combination with recurrent late decelerations or recurrent variable decelerations 5 6.…”
Section: Methodsmentioning
confidence: 99%